Streptomyces fodineus sp. nov., an actinobacterium with antifungal activity isolated from mine area soil. Issue 5 (21st March 2019) - Kim, Min-Kyeong; Kang, Hye-Jeong; Roh, Su Gwon; Park, Ji Sun; Kim, Seung Bum
Abstract : A novel actinobacterial strain producing an antifungal substance was isolated from a sample of acidic mine area soil, and its taxonomic position was evaluated. The novel strain, designated TW1S1 T, formed white-grey aerial mycelium and yellow substrate mycelium on oatmeal agar. Growth occurred at 10–45 °C (optimum, 30 °C), pH 4–9 (pH 6–7) and in the presence of up to 8 % (w/v) NaCl. Melanin was produced on peptone–yeast extract–iron agar. Phylogenetic analysis based on its 16S rRNA gene sequence indicated that the novel strain should be assigned to the genus Streptomyces, and the closest species was Streptomyces puniciscabiei S77 T with 99.1 % sequence similarity, which was followed by Streptomyces durhamensis NRRL B-3309 T (99.0 %), Streptomyces filipinensis NBRC 12860 T (98.9 %) and Streptomyces yaanensis Z4 T (98.7 %). The chemotaxonomic properties were consistent with those of Streptomyces .ll -Diaminopimelic acid was the diagnostic diamino acid, and alanine, glutamic acid and glycine were present in the peptidoglycan. The cell-wall hydrolysate also contained galactose, glucose, mannose and ribose. The predominant isoprenoid quinones were MK-9(H4 ) and MK-9(H6 ), the major polar lipids were phosphatidylglycerol and an unidentified phospholipid, and the main fatty acids were iso-C16 : 0 and anteiso-C15 : 0 . However, strain TW1S1 T could be distinguished from its neighbouring species by its phenotypic properties. In addition, the genome-based comparison with the closest species indicated that strain TW1S1 T should be recognized as a separate species. The phylogenetic, phenotypic and chemotaxonomic as well as genomic evidence supported that TW1S1 T represents a novel species of Streptomyces, for which the name Streptomyces fodineus sp. nov. is proposed (type strain, TW1S1 T = KCTC 49013 T = JCM 32404 T ).